2020
DOI: 10.37311/jnj.v2i2.8463
|View full text |Cite
|
Sign up to set email alerts
|

Shock Index (SI) dan Modified Shock Index (MSI) sebagai Prediktor Outcome pada Pasien Gawat Darurat: Systematic Review

Abstract: Shock Index dan Modified Shock Index merupakan parameter non invasif dapat digunakan dalam pemantauan status hemodinamika pasien untuk menilai hasil klinis dan memprediksi mortalitas pasien gawat darurat, sehingga dapat membantu penatalaksanaan pada waktu yang tepat terutama dalam pelaksanaan triase di departemen darurat. Penelitian ini bertujuan untuk mengetahui penggunaan parameter Shock Index dan Modified Shock Indeks dalam memprediksi hasil klinis pasien gawat darurat, mengetahui perbandingan penggunaan pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The Shock Index (SI) and Modified Shock Index (MSI) are new score predictors that have emerged as simpler and easier tools for predicting mortality in ACS [ 8 ]. SI and MSI are now used in the emergency settings, including ACS patients [ 9 – 11 ]. In a study comparing MSI with SI, it was found that MSI was more accurate than SI for predicting mortality and major cardiovascular events in patients with NSTEMI who received percutaneous coronary intervention (PCI) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Shock Index (SI) and Modified Shock Index (MSI) are new score predictors that have emerged as simpler and easier tools for predicting mortality in ACS [ 8 ]. SI and MSI are now used in the emergency settings, including ACS patients [ 9 – 11 ]. In a study comparing MSI with SI, it was found that MSI was more accurate than SI for predicting mortality and major cardiovascular events in patients with NSTEMI who received percutaneous coronary intervention (PCI) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 SI and MSI are now used to estimate mortality in the population of the emergency department, including ACS patients. [9][10][11] In a study comparing MSI with SI, it was determined that MSI was more accurate than SI for predicting mortality and major cardiovascular events in patients with NSTEMI who received percutaneous coronary intervention (PCI). 12 The SIC score is calculated using the following formula: (SI×100)-estimated clearance ratio (CCr).…”
Section: Introductionmentioning
confidence: 99%
“…Shock index (SI) is mark which obtained from the calculation of heart rate (HR) shared with pressure systolic blood pressure (SBP) used to evaluate the hemodynamic stability of acute patients . SI can used for status monitoring dynamics patient so that can evaluate results clinical And predict patient mortality bad emergency, so that can help in management on right time while the patient is in the ER (Pomalango, 2016) . Research conducted by Torobi (2016) explains that S1 > 0.9 will cause death at <24 hours and 48 hours (Torabi, Moeinaddini, et al, 2016) .…”
Section: Introductionmentioning
confidence: 99%